RETRACTED: ROLE OF SNALL-SIZED ENTERPRISES IN INNOVATIVE ECONOMICS OF DEVELOPED AND DEVELOPING COUNTRIES - A.G. Komissarov (Модернизация, инновация, развитие, 2016)
Retracted articleAt present, the share of small-sized enterprises in Gross Domestic Product and their development rates in Russia are considerably lower than those in economically developed countries. The state regulates market relations there only through legislation. In Russia and in other countries with transition economics small-sized enterprises should get essential legal, financial and economical support on the part of the state. Russian entrepreneurship innovative development ways are shown.